The Influence of Operating Cash Flow, Net Income, Depreciation Expenses, and Amortization Expenses on Cash Flow Forecasting at PT. Bank XYZ - Aisyah Nurul Aini; Herlina Napitupulu; Sukono Sukono (Research Collaboration Community (RCC), 2023)
The cash flow statement is part of a company's financial statements produced in an accounting period that shows the company's cash inflows and outflows. This study aims to analyze the effect of operating cash flow variables, net income, depreciation expense, and amortization expense on forecasting future cash flows. This research uses quantitative research using secondary data with a descriptive approach, which is analyzed using the Multiple Linear Regression method with SPSS assistance. The object used is PT. Bank XYZ for the period January 2019 to February 2023. The results show that operating cash flow affects forecasting future cash flows, net profit does not affect forecasting future cash flows, depreciation expense does not affect forecasting future cash flows, and amortization expense does not affect forecasting future cash flows. However, operating cash flow, net profit, depreciation expense, and amortization expense simultaneously affect the cash flow forecasting results. Based on the forecasting results, which have a MAPE value of 17.43%, it can be concluded that the forecasting results have good forecasting abilities.